Literature Review: the Effect of Ajwa Dates on Hemoglobin Levels in Perimenopause Women - Cahyani, Eka Saputri Ananda; Andi Mappaware, Nasrudin; Arfah, Arni Isnaini; Irwan, Irwan; Nulanda, Mona; Yuniati, Lisa (Journal La Medihealtico, 2024)
Ajwa dates or often called prophet dates are types of dates that grow in Saudi Arabia / Al-Madinah Al-Munawara and have significant value in healing several diseases. The content of active substances contained in date extracts such as vitamins B1, B2, nicotinic acid, vitamin complex A, magnesium, calcium and iron which has a function to help the formation of hemoglobin. Perimenopause is an indefinite period of time that surrounds the final years of a woman's reproductive life, usually between the ages of 30-40 years when estrogen levels slowly decline causing menstrual abnormalities. The decrease in estrogen levels in perimenopausal women causes excessive blood loss so that iron deficiency anemia will occur. Objective : To determine the effect of consumption of ajwa dates (Pheonix Dactylifera L) on hemoglobin levels in perimenopausal women. Method : Literature Review with Design Narrative review. Results : Based on the results of research from several literatures that discuss the effects of giving Ajwa Dates (Phoenix Dactylifera L) before and after administration, it shows that there are differences in hemoglobin levels. Especially in perimenopausal women who are prone to iron deficiency anemia because Ajwa dates contain high iron, which increases hemoglobin levels. So it is highly recommended for consumption. Conclusion : Ajwa Dates (Phoenix Dactylifera L) can increase hemoglobin levels in perimenopausal women.